2018
DOI: 10.1542/peds.2018-0277
|View full text |Cite
|
Sign up to set email alerts
|

Appropriateness of Pediatrics Case Reports Citations

Abstract: These results reveal that most citations of case reports are appropriate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Bryan Sisk from Washington University in St Louis, while working as an editorial fellow for Pediatrics, decided with colleagues to study how case reports from Pediatrics are cited. 28 He found that the majority provide a clear proviso that the citation is a case report and with appropriate caution, regarding its applicability, only rarely have they been cited as scientific evidence.…”
Section: What Is To Be Gained or Lost By Eliminating Case Reports?mentioning
confidence: 99%
“…Bryan Sisk from Washington University in St Louis, while working as an editorial fellow for Pediatrics, decided with colleagues to study how case reports from Pediatrics are cited. 28 He found that the majority provide a clear proviso that the citation is a case report and with appropriate caution, regarding its applicability, only rarely have they been cited as scientific evidence.…”
Section: What Is To Be Gained or Lost By Eliminating Case Reports?mentioning
confidence: 99%